Complement protein C1q stimulates hyaluronic acid degradation via gC1qR/HABP1/p32 in malignant pleural mesothelioma - Balduit, Andrea; Vidergar, Romana; Zacchi, Paola; Mangogna, Alessandro; Agostinis, Chiara; Grandolfo, Micaela; Bottin, Cristina; Salton, Francesco; Confalonieri, Paola; Rocca, Andrea; Zanconati, Fabrizio; Confalonieri, Marco; et al. (Frontiers in Immunology, 2023)
Complement component C1q can act as a pro-tumorigenic factor in the tumor microenvironment (TME). The TME in malignant pleural mesothelioma (MPM) is rich in C1q and hyaluronic acid (HA), whose interaction enhances adhesion, migration and proliferation of malignant cells. HA-bound C1q is also capable of modulating HA synthesis. Thus, we investigated whether HA-C1q interaction would affect HA degradation, analyzing the main degradation enzymes, hyaluronidase (HYAL)1 and HYAL2, and a C1q receptor candidate. We first proceeded with the characterization of HYALs in MPM cells, especially HYAL2, since bioinformatics survival analysis revealed that higher HYAL2 mRNA levels have an unfavorable prognostic index in MPM patients. Interestingly, Real-Time quantitative PCR, flow cytometry and Western blot highlighted an upregulation of HYAL2 after seeding of primary MPM cells onto HA-bound C1q. In an attempt to unveil the receptors potentially involved in HA-C1q signaling, a striking co-localization between HYAL2 and globular C1q receptor/HABP1/p32 (gC1qR) was found by immunofluorescence, surface biotinylation and proximity ligation assays. RNA interference experiments revealed a potentially regulatory function exerted by gC1qR on HYAL2 expression, since C1QBP (gene for gC1qR) silencing unexpectedly caused HYAL2 downregulation. In addition, the functional blockage of gC1qR by a specific antibody hindered HA-C1q signaling and prevented HYAL2 upregulation. Thus, C1q-HA interplay is responsible for enhanced HYAL2 expression, suggesting an increased rate of HA catabolism and the release of pro-inflammatory and pro-tumorigenic HA fragments in the MPM TME. Our data support the notion of an overall tumor-promoting property of C1q. Moreover, the overlapping localization and physical interaction between HYAL2 and gC1qR suggests a potential regulatory effect of gC1qR within a putative HA-C1q macromolecular complex.